New Techniques for Brand Management in the Healthcare Sector - Ramani, Jayeshkumar (Digital Repository of Theses, 2025)
This research looks at the new strategies in running healthcare practices with an emphasis on incorporating artificial intelligence (AI), green practices, and generation perspectives into brand frameworks. Contemporary healthcare institutions are confronted with the double mandate of satisfying patients' needs and establishing their brand in a competitive market. Through the use of a mixed-methods approach, the present study applies qualitative and quantitative data—derived from formal questionnaires, face-to-face interviews, and group work—to provide a wide overview of brand transformation in the healthcare sector. The research reveals that AI indeed plays a role of innovation in brand strategy, maximizing operational efficiency alongside patient engagement. Research also shows that while sustainability is a very ethical value, its role in the brand image is less than that of AI. Moreover, findings of generations show that the form of customized branding techniques varies with an emphasis on digital and mental health-based techniques being acceptable to the younger generations and openness and personal interaction being valued by the older generations. The thesis contributes to literature by covering less-explored intersectional spaces—i.e., AI ethics, patient trust, and intergenerational relationships—of healthcare branding. Based on evidence-informed findings, this thesis not only contributes to scholarship but also provides actionable recommendations to healthcare marketers and policymakers striving for the development of brand trust, ethical engagement, and tech uptake.